Exogenous and Endogenous Plasma Levels of Epinephrine During Dental Treatment Under Local Anesthesia. Issue 1 (January 1993) - Lipp, M.; Fuder, H.; Dick, W.; Stanton-Hicks, M.; Daubländer, M.
Abstract : Background and Objectives: To determine serum levels of catecholamines after local anesthesia for dental treatment, we used tritium-labeled epinephrine as a vasoconstrictor for dental local anesthesia. Methods: Twenty healthy male outpatients undergoing standardized dental treatment (deep scaling) were studied. In all patients, only one quadrant was anesthetized even though the treatment was performed on all teeth. Two milliliters of articaine 4% (amide anesthetic) with 20 μg epinephrine was used as local anesthetic. Of the total epinephrine administered, 1.2% (100 μCi) consisted of tritium-labeled epinephrine. Blood samples were drawn through a central venous catheter before and at frequent intervals after the local anesthetic solution was administered. Results: A dramatic increase in exogenous epinephrine was observed in four patients during injection (up to 6937 pg/mL). The other 16 patients demonstrated a continuous increase in applied epinephrine that peaked on average at the 7th minute (631.5 ± 41.4 pg/mL). A second increase occurred after the beginning of the dental procedure. The mean total epinephrine levels were always higher than those of the applied epinephrine. Extrasystoles were observed in two of four and tachycardia in three of four patients with high plasma levels of applied epinephrine. Increases in total epinephrine were associated with exogenous catecholamine administration, whereas the dental treatment did not significantly influence the plasma levels. Conclusion: Despite aspiration in 20% of the patients, an unintended intravascular injection occurred. Although healthy young men tolerated large increases in central plasma epinephrine levels surprisingly well, this may not be the case in patients with concurrent cardiovascular disease. Patients at cardiovascular risk should be under continuous monitoring when an epinephrine-containing solution is applied.